Tafsir Aplikatif: Poligami dalam Perspektif Ulama Klasik dan Kontemporer - Diana, Wulan Nur; Siti Nur Khoiriyah (Kopertais Wilayah III Yogyakarta, 2024)
Polygamy has never been discussed, it can be seen from various perspectives, from a socio-cultural perspective to a theological-interpretive perspective. This article focuses on how ulama, from the past to the present, discuss polygamy. This research method is a library research using data analysis techniques. The aim of this research is to find out how they interpret the QS. al-Nisa' [4]: ​​3 which textually mentions the issue of polygamy from the perspective of classical and contemporary scholars. This research uses primary data sources and secondary data sources. The results of the research conclude that in the Islamic view, polygamy is permissible if it meets the conditions that are clear in the Koran, namely, being able to act fairly. Fairness referred to here includes several parts, namely: fairness in the distribution of time, fairness in living, fairness in housing and fairness in child expenses. There are two views of ulama, namely classical ulama and contemporary ulama, they argue about polygamy in Q.s An-nisa verse 3 as follows. First, classical ulama Zhahiriyah, Ibn al-Shabbagh, al-Umran, al-Qasim ibn Ibrahim, and some Shia groups allow polygamy with a maximum limit of 9 wives. Second, the views of contemporary ulama, according to Muhammmad Abduh and Qasim Amin, tolerate the practice of polygamy in emergency conditions. The emergency in question, among other things, is: the wife is infertile so she cannot give birth to offspring, the wife suffers from a permanent disease which causes the wife to be unable to carry out her obligations as a wife. Keyword: Al-quran, Polygamy, Contemporary Ulama, Classical Ulama